Legal problems concerning national park’s administrative management system in Thailand - จิตบาน, พงษ์ศิริ; เลื่อนฉวี, พรชัย (Community and Social Development Journal, 2015)
The objective of this article was to study the legislative measure related to administrative management system of the national park in Thailand according to National Park Act, B.E. 2504 and The Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 and other countries in accordance with Natural Parks Law C.E. 1957 (Japan), Natural Parks Act C.E 1980 (Republic of Korea), National Park Law C.E. 2011 (Republic of China), National Parks Act C.E.1980 (New Zealand) and National Parks Act C.E.1985 (Canada) . Moreover, it included studying and analyzing Legal problems concerning national park’s administrative management system in Thailand according to National Park Act, B.E.2504 and The Enhancement and Conservation of National Environmental Quality Act, B.E.2535, comparing with the National Park in foreign countries mentioned above conforming with fundamental concepts, principles and legal theories of public law in terms of administrative management system in National Park, such as the theory of governmental functions, public services, the principle of public participation, etc. Additionally, this study was for advising on solutions applicable to the national park’s administrative management according to National Park Act, B.E.2504. The aforementioned objectives can be taken as principles and guidelines to governmental sectors and officials in the national park for sustainable administrative management.